PENGARUH LITERASI KEUANGAN DAN LINGKUNGAN SOSIAL TERHADAP PERENCANAAN KEUANGAN PRIBADI - Muhammad Noor Fuadi; Sri Trisnaningsih (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2022)
Several survey results note that Indonesian people still carry out financial planning, in line with the diverse needs it is important to have the ability and skills to make finances. The purpose of this study was to examine and analyze the effect of financial literacy and social environment on personal financial planning for students of the UPN